Revisiting An Islamic Approach to Humanities: A Critical Review - Sebastian Herman; Mohd Mahyudi bin Mohd Yusop (AL-FALAH : Journal of Islamic Economics, 2021)
Purpose: The study aims to develop a relevant counter-argument and supporting justification on ideas offered by Zaman (2014) in his paper titled "An Islamic Approach to Humanities." Design/Method/Approach: This study adopts a quantitative approach in form of a literature survey, discourse and critical content analysis. For achieving the goal, we capitalize on Ghazi (2006) to support the argument that the source of knowledge is not only through observations. Kalin (2016) and Zarkasyi (2018) are being used to show that Islam encourages reasoning and observations. To support the argument that Islamic economics can be positivistic, we use Abdullahi (2018) as a related paper to deal with that issue. Findings: The study found that Islamic Economics can use the tools of logical positivists in its observation as long as such tools do not contradict the logical structure of the Islamic worldview. Social science like Islamic economics is only an avenue to see the expression of free will that Allah gives to the human being by observing the pattern of human behavior. When the results can describe closer to reality, it can survive and support the development of social science itself. Originality/Values: The main contribution of this study is to clarify the position of Islamic economics on the logical positivism method and its implication in value integration.